Quality improvement project to reduce beta-D-glucan turnaround times in an NHS pathology network - Nathan Proudlove; Cassie Pope; Madeline Stone (BMJ Open Quality)
Beta-D-glucan (BDG) is a cell wall component of many fungi, detecting this in patients’ serum permits early diagnosis of invasive fungal infections, particularly in patients with haematological malignancy. In critically ill patients in an intensive-care unit, where the prevalence of invasive fungal infection is lower, the high negative predictive value of BDG facilitates withholding or discontinuation of empirical antifungal therapy, contributing to antifungal stewardship. However, for the results of BDG testing to impact patient management, they need to be available within a clinically useful timeframe.The South West London Pathology (SWLP) network routinely sent samples for BDG testing from hospital trusts in our area to the UK Health Security Agency Mycology Reference Laboratory (MRL) at Bristol for analysis. In 2021, the mean turnaround time (TAT) was more than two times the 5-working-days standard stated in the SWLP user handbook. In this quality improvement project (QIP), we identified that the greatest delay was the MRL posting hardcopy reports. We investigated electronic reporting, first for all patient samples, and then only for intensive-care patients. However, we found that information technology (IT) and staffing limitations meant this was not viable.We then investigated commercial solutions and identified an innovative assay, which enabled the implementation of in-house BDG testing that was a good fit with our available staffing resource and laboratory environment. Our aim was to achieve at least 90% of BDG results authorised within 5 working days of sample receipt. Our QIP improved performance on this from 0.88% to 92.8% and reduced the mean TAT from 11.6 to 2.5 days and at lower unit cost. The change has been well received by our laboratory staff, and our pathology operational leads have had very positive feedback from our clinical teams and our antifungal steward.